2022
DOI: 10.1159/000525468
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell and Acellular Pertussis Vaccine: Reflections on Efficacy

Abstract: Pertussis is a common respiratory infection caused by the bacterium Bordetella pertussis. Although most cases occur in developing countries, it is considered endemic globally. The World Health Organization estimates there are 20 to 40 million cases of pertussis annually. Pertussis vaccines played a pivotal role in reducing the burden of pertussis disease as well as in infant morbidity and mortality. Although the two forms of pertussis vaccine are effective, each has its advantages and drawbacks. This paper aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…An example is the hepatitis B vaccine, which employs a protein from the surface of the virus as a subunit ( 156 ). Another example is the acellular pertussis vaccine, which uses several purified proteins from B. pertussis ( 219 ).…”
Section: Types Of Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is the hepatitis B vaccine, which employs a protein from the surface of the virus as a subunit ( 156 ). Another example is the acellular pertussis vaccine, which uses several purified proteins from B. pertussis ( 219 ).…”
Section: Types Of Vaccinesmentioning
confidence: 99%
“…This method increases the immunogenicity of polysaccharides, especially in infants < 2 years of age. Polysaccharide-protein conjugation allows the immune system to recognize and respond more effectively, producing polysaccharide-specific antibodies and generating memory cells ( 219 ). The pneumococcal, meningococcal, and H. influenza type b conjugate vaccines are successful examples of this type of vaccine ( 220 ).…”
Section: Types Of Vaccinesmentioning
confidence: 99%
“…Although both antigens provide overall comparable immunogenicity, wP is much less expensive to produce than aP (requiring manufacturing of up to five different individual antigens), making it preferable for use in LMICs. 65 The development of combination pediatric vaccines containing both IPV and wP is thus a challenging formulation goal. 62 , 66 , 67 Kraan et al observed immediate temperature-dependent loss of efficacy upon resuspension of lyophilized IPV, with pentavalent vaccine suggesting that the thimerosal-induced destabilization occurs too quickly for resuspension to be a feasible option.…”
Section: Low-cost and Next-generation Ipv Vaccine Formulationsmentioning
confidence: 99%
“…The structure of lipid A determines the downstream immune response; therefore, in the case of vaccination, the ability to generate novel lipid A structures that activate specific inflammatory pathways would make for powerful adjuvants ( 43 , 48 , 49 ). It has been appreciated that the potent immune response of the wP formulation results from both the number of antigens available and the immunostimulatory effect of B. pertussis ’ lipooligosaccharide (LOS) molecule ( 50 , 51 ). We hypothesize that the use of a vaccine formula containing an engineered lipid A mimetic could confer the ideal aspects of both types of pertussis vaccines: the protective immunity of wP and the safety of aP.…”
Section: Introductionmentioning
confidence: 99%